2017
DOI: 10.1038/s41598-017-04997-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term cultivation of transgenic Bt rice (Kefeng-6) on soil microbial functioning and C cycling

Abstract: Understanding how soil ecosystem responds to transgenic Bacillus thuringiensis (Bt) rice is necessary for environmental risk assessment. While the influences of short-term cultivation of Bt rice on soil properties have been reported previously, little is known about the long-term effects of Bt rice on soil ecosystems. In this study, soil samples were taken from a long-term rice cultivation site in Fujian Province, China, where transgenic Bt rice (Kefeng-6) and its non-Bt parent breed (Minghui-86) had been cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…Further, soil pH was the strongest predictor of soil fungal community composition, followed closely by Bt protein content, suggesting that Bt protein introduced by root exudates did not impact fungal community composition more strongly than soil pH. Notably, several studies have shown that Bt protein expressed by Bt crops does not persist in the soil after long-term cultivation of Bt crops [ 10 , 47 , 48 ]. Moreover, environmental factors and cotton growth traits are specific at different growth stages, which affect the diversity and dynamics of rhizosphere microbial communities differently.…”
Section: Discussionmentioning
confidence: 99%
“…Further, soil pH was the strongest predictor of soil fungal community composition, followed closely by Bt protein content, suggesting that Bt protein introduced by root exudates did not impact fungal community composition more strongly than soil pH. Notably, several studies have shown that Bt protein expressed by Bt crops does not persist in the soil after long-term cultivation of Bt crops [ 10 , 47 , 48 ]. Moreover, environmental factors and cotton growth traits are specific at different growth stages, which affect the diversity and dynamics of rhizosphere microbial communities differently.…”
Section: Discussionmentioning
confidence: 99%
“…Each soil sample was divided into three parts for DNA extraction, environmental factor determination, and soil enzyme activity determination. Soil organic carbon (SOC), total nitrogen (TN), and available phosphorus (AP) content was then measured as previously described (Bremner and Tabatabai, 1972 ; Soon and Abboud, 1991 ; Zhaolei et al, 2017 ), and soil enzyme kits were used to determine soil urease (S-U), soil sucrase (S-SC), soil catalase (S-CAT), and soil acid phosphatase (S-ACP) (Wang et al, 2014 ; Hou et al, 2020 ). Each soil sample was analyzed in three replicates, 0.5 g per sample.…”
Section: Methodsmentioning
confidence: 99%
“…The impact of Bt-toxin on soil microorganisms is either inconsistent or negligible under various agro-climatic conditions (Kapur et al 2010;Hu et al 2013;Velmourougane & Sahu 2013). However, the continuous growing of transgenic crops in the same location might enhance the toxin's concentration to a level that might influence the composition and activity of soil microbial communities and microbiological properties (Zhaolei et al 2017;Li et al 2018). Existing literature present inconclusive data on this issue.…”
Section: Introductionmentioning
confidence: 99%